INFLATION AND NUMBER OF TAXABLE ENTREPRENEURS (NTE) TOWARDS ADMISSION OF VALUE ADDED TAX (VAT) - Rima Sundari; Fajar Maulana (TRIKONOMIKA, 2018)
This study aims is to determine the effect of macroeconomic variables on inflation and the Number of Taxable Entrepreneurs (NTE) both partially and simultaneously on the receipt of Value Added Tax (VAT). This study uses a quantitative approach. The sampling technique used is purposive sampling. The sample in this study were 3 KPPs in West Java that are KPP Majalaya, KPP Sukabumi, and KPP Tasikmalaya with monthly data of the research period July 2013 - June 2016, the number of sample data used was 108, and analyzed using multiple regression analysis. The results of the study show that inflation partially has a negative and significant effect on VAT receipts. While simultaneously inflation, the number of NTE has a positive and significant effect on VAT receipts